Correlation between the Leisure Time Physical Activity and the Physical Fitness of Normal Individuals Working in the Corporate Sector - Easow, Betsy Ann; Swaminathan, Narasimman (Red Flower Publication Private Limited, 2015)
This study was conducted to find out the correlation between the physical activity at work and leisure time physical activity of normal individuals working in the corporate sector. A total of 97 employees of various Banks and Institutes in Mangalore were recruited for this. International Physical Activity Questionnaire (IPAQ) was used to measure the physical activity levels and the Rockport One Mile Walk Test was used to measure their physical fitness. The result showed a weak correlation between leisure time physical activity and physical activity at work. It was also found that more than half the study population lacked leisure time physical activity. This study suggests that there should be more awareness programmes to inform the importance of physical activity during leisure time and also steps to encourage activity at work should be taken up.